IBD in pregnancy: recent advances, practical management. Issue 3 (19th May 2020) - Selinger, Christian P; Nelson-Piercy, Catherine; Fraser, Aileen; Hall, Veronica; Limdi, Jimmy; Smith, Lyn; Smith, Marie; Nasur, Reem; Gunn, Melanie; King, Andrew; Mohan, Aarthi; Mulgabal, Khasia; et al.
Abstract : Inflammatory bowel disease (IBD) poses complex issues in pregnancy, but with high-quality care excellent pregnancy outcomes are achievable. In this article, we review the current evidence and recommendations for pregnant women with IBD and aim to provide guidance for clinicians involved in their care. Many women with IBD have poor knowledge about pregnancy-related issues and a substantial minority remains voluntarily childless. Active IBD is associated with an increased risk of preterm birth, low for gestation weight and fetal loss. With the exception of methotrexate and tofacitinib the risk of a flare outweighs the risk of IBD medication and maintenance of remission from IBD should be the main of care. Most women with IBD will experience a normal pregnancy and can have a vaginal delivery. Active perianal Crohn's disease is an absolute and ileal pouch surgery a relative indication for a caesarean section. Breast feeding is beneficial to the infant and the risk from most IBD medications is negligible.